EDUKASI MANAJEMEN STRES UNTUK MENINGKATKAN KETAHANAN DIRI MERAWAT PADA CAREGIVER KELUARGA LANSIA DENGAN PENYAKIT KRONIK DI LEMPAKE KOTA SAMARINDA - Bahtiar Bahtiar; Iskandar Muda; Khumaidi Khumaidi; Muhammad Aminuddin; Dwi Nopriyanto; Ida Widiastuti (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2022)
Background: The elderly in Indonesia are predominantly cared for by elderly families. Elderly families often have difficulty caring for and assisting the elderly, so it has the potential to trigger psychological problems. Purpose: This community service is carried out to improve the knowledge, attitudes, and skills of elderly family caregivers in implementing stress management. Methods: The activity was carried out for two days with a lecture, discussion, and demonstration approach. Results: There was increased knowledge, attitudes, and skills before and after giving stress management education to elderly family caregivers. This activity can be applied as a mental health promotion activity for elderly family caregivers with chronic diseases. Conclusion: This community service activity can increase the knowledge, attitudes, and skills of caregivers for elderly families with chronic diseases so that they are expected to be able to increase family resilience.